2019
DOI: 10.1016/j.cell.2019.03.046
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Degradation of Circular RNAs Regulate PKR Activation in Innate Immunity

Abstract: Highlights d circRNAs are globally degraded by activated RNase L upon viral infection d Many circRNAs tend to form 16-26 bp duplexes and act as endogenous PKR inhibitors d The RNase L-mediated circRNA degradation is required for PKR activation d circRNA reduction and aberrant PKR activation are found in autoimmune disease SLE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
544
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 605 publications
(559 citation statements)
references
References 58 publications
12
544
2
1
Order By: Relevance
“…The EMBO Journal 38: e100836 | 2019 blood mononuclear cells derived from systemic lupus erythematosus patients (Liu et al, 2019). In addition to degradation, circRNAs might be eliminated from cells by exocytosis.…”
Section: Sequence-vs Protein-driven Exon Circularizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The EMBO Journal 38: e100836 | 2019 blood mononuclear cells derived from systemic lupus erythematosus patients (Liu et al, 2019). In addition to degradation, circRNAs might be eliminated from cells by exocytosis.…”
Section: Sequence-vs Protein-driven Exon Circularizationmentioning
confidence: 99%
“…The EMBO Journal 38: e100836 | 2019 ª 2019 The Authors (Liu et al, 2019). These hairpins are bound by RBPs responsible for intracellular immune response.…”
Section: Circrna Properties and Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…PKR thus needs to be readily activatable yet maintained in an inactive state in uninfected cells to prevent inappropriate reactions and autoimmunity. Previous work has shown that PKR activation can be blocked upon binding the adenovirus small noncoding VAI RNA (Kitajewski et al, 1986) or short (16-33 bp) dsRNAs (Zheng and Bevilacqua, 2004), and Liu et al (2019) now find that many endogenous circular RNAs are able to bind PKR. Interestingly, when the binding profiles of linear and circular RNAs of the same sequence were compared, circular RNAs bound much more strongly to PKR.…”
mentioning
confidence: 89%
“…Most other individual circular RNAs are expressed at exceedingly low levels, so it has remained unclear what biological function (if any) they exert. In this issue of Cell, Liu et al (2019) reveal that circular RNAs can collectively bind and suppress activation of the kinase PKR, thereby controlling innate immune responses. The innate immune system is the first line of defense against invading pathogens and involves a set of receptors that recognize pathogen structures (reviewed in Mogensen, 2009).…”
mentioning
confidence: 99%